NADPH oxidase inhibitor development for diabetic nephropathy through water tank model - Hye Eun Lee; Seunghwan Shim; Yongseok Choi; Yun Soo Bae (The Korean Society of Nephrology, 2022)
Oxidative stress can cause generation of uncontrolled reactive oxygen species (ROS) and lead to cytotoxic damage to cells and tissues. Recently, it has been shown that transient ROS generation can serve as a secondary messenger in receptor-mediated cell signaling. Although excessive levels of ROS are harmful, moderated levels of ROS are essential for normal physiological function. Therefore, regulating cellular ROS levels should be an important concept for development of novel therapeutics for treating diseases. The overexpression and hyperactivation of NADPH oxidase (Nox) can induce high levels of ROS, which are strongly associated with diabetic nephropathy. This review discusses the theoretical basis for development of the Nox inhibitor as a regulator of ROS homeostasis to provide emerging therapeutic opportunities for diabetic nephropathy.